Ten-eleven translocation-2 affects the fate of cells and has therapeutic potential in digestive tumors - Feng Wang (KeAi Communications Co., Ltd., 2019)
Ten-eleven translocation (TET) methylcytosine dioxygenases catalyze the oxidative reactions of 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine (5-fC), and 5-carboxylcytosine (5-caC), which are intermediate steps during DNA demethylation. It is reported that somatic mutations of TET2 gene are identified in a variety of human tumors, especially in hematological malignancies. The tendency and mechanism of cellular differentiation in different systems are affected by TET2 via regulation of associated gene expression or maintenance of demethylated state. TET2 acts as a critical driver of tumorigenesis through the conversion of 5-mC to 5-hmC and successive oxidation products. Sometimes, it requires special interactions and cofactors. Here, we reviewed recent advances in understanding the function of TET2 proteins in regulating cell differentiation, and its role in various tumors focusing on several digestive cancers. Keywords: Demethylation, Ten-eleven translocation-2, Differentiation, Digestive tumors